(untitled) (Web of Teachers: Inderscience Research, 2025)
Independent study is a pivotal approach in fostering professional competence among students, enabling them to acquire knowledge, skills, and attitudes essential for career success. This article explores the role of independent study in developing professional competence, emphasizing its impact on critical thinking, self-discipline, and adaptability. Through a systematic literature review and analysis, we identify key strategies, benefits, and challenges of independent study, supported by empirical evidence. Findings suggest that structured independent study enhances students’ ability to solve complex problems, manage time effectively, and cultivate lifelong learning habits. Recommendations for educators and institutions include integrating guided independent study frameworks and leveraging technology to support student autonomy.